Low expression of H3K27me3 is associated with poor prognosis in conventional chordoma - Wei, Jie; Wu, Jianfeng; Yin, Zhiyong; Li, Xia; Liu, Yixiong; Wang, Yingmei; Wang, Zhe; Xu, Chao; Fan, Linni (Frontiers in Oncology, 2022)
Purpose: Chordoma is a rare and locally invasive neoplasm, and the prognostic factors are limited. Deregulation of Histone 3 lysine 27 (H3K27) trimethylation (H3K27me3) is considered to be related with poor prognosis in some tumors. The purpose of this study was to detect the expression of H3K27me3 in chordomas and analyze the correlation with clinicopathological features and explore the roles as potential prognostic markers and therapeutic targets. Material and Method: Specimens of 162 chordoma patients were enrolled in a tissue microarray (TMA) in order to assess the immunohistochemical staining by H3K27me3 antibodies. Correlations between H3K27me3 expression and clinicopathological features were analyzed. Clinical data of the patients were correlated and survival analysis was performed. Kaplan-Meier survival curves and log-rank test were used to analyze the recurrence-free survival (RFS) and overall survival (OS). Multivariate Cox regression analyses were used to identify potential prognostic factors. Results: The expression of H3K27me3 was lower in 37 chordoma patients (37/162, 22.8%), and higher in 125 patients (125/162, 77.2%). H3K27me3-low expression significantly correlated with spine location (P < 0.05), conventional histological subtype (P < 0.05), recurrence (P < 0.05), and death (P < 0.05). Log-rank test showed that H3K27me3-low expression was associated with poor RFS and OS (P < 0.05) in chordoma patients. Cox multivariate analysis revealed that low expression of H3K27me3 was an independent predictor of poor OS (P < 0.05) and RFS (P < 0.05) in chordoma patients. Conclusions: Our study indicates that low expression of H3K27me3 might be considered as a predictor for poor prognosis and recurrence, and it may provide a potential therapeutic target for chordoma patients.